Loop Mediated Isothermal Amplification (LAMP) for Embryo Sex Determination in Pregnant Women at Eight Weeks of Pregnancy - MA Almasi; G Almasi (JRI, 2017)
Background: In human, SRY (sex-determining region of the Y chromosome) is the major gene for the testis-determining factor which is found in normal XY males and in the rare XX males, and it is absent in normal XX females and many XY females. There are several methods which can indicate a male genotype by the presence of the amplified product of SRY gene. The aim of this study was to identify the SRY gene for embryo sex determination in human during pregnancy using loop mediated isothermal amplification (LAMP) method. Methods: A total of 15 blood samples from pregnant women at eight weeks of pregnancy were collected, and Plasma DNA was extracted. LAMP assay was performed using DNA obtained for detection of SRY gene. Furthermore, colorimetric LAMP assay for rapid and easy detection of SRY gene was developed. Results: LAMP results revealed that the positive reaction was highly specific only with samples containing XY chromosomes, while no amplification was found in samples containing XX chromosomes. A total of 15 blood samples from pregnant women were seven male embryos (46.6%) and eight female embryos (53.4%). All used visual components in the colorimetric assay could successfully make a clear distinction between positive and negative ones. Conclusion: The LAMP assay developed in this study is a valuable tool capable of monitoring the purity and detection of SRY gene for sex determination.